The Effect of Kidney Transplantation on Pulmonary Hypertension in End-stage Kidney Disease Patients on Hemodialysis - Christine Mary Jane; K. Vinod Kumar; R. Anil Kumar; V. Narayanan Unni; Bipi K. Prasannan; Jojo K. Pullockara; U. R. S. Vishnu Dev (Indian Journal of Transplantation)
Introduction: Pulmonary hypertension (PH) is highly prevalent in chronic kidney disease (CKD) patients, especially those undergoing hemodialysis. PH is a strong independent predictor of mortality in dialysis patients. Kidney transplantation (KT) is the best treatment modality for reversing adverse cardiac effects of CKD. Methods: A prospective cohort study was done in end-stage kidney disease (ESKD) patients on hemodialysis with PH (defined as pulmonary artery systolic pressure [PASP] of 35 mmHg or above) who subsequently underwent KT. Follow-up echocardiogram was done at an average of 15 months post KT. Results: A total of 277 patients underwent KT, out of which 95 had PH (prevalence 34.3%). Our study included 65 patients with PH who consented for the study. There was a significant improvement in PH as evidenced by a reduction in PASP (PASP pre KT 44.8 [±9.91] post KT 32.77 [±6.33], P = 0.001). 72.3% of patients achieved normal pulmonary pressures. There was also a significant improvement in ejection fraction (63.01 [±7.4] vs. 65.06 [±5.61], P = 0.04) and left atrial diameter (3.9 [±0.45] vs. 3.52 [±0.51], P = 0.001) post KT. There was an improvement in mean hemoglobin level (10.4 [±2.17] vs. 13.5 [±2.13], P = 0.001), serum calcium levels (serum Ca 8.76 [±0.72] vs. 9.19 [±0.82], P = 0.001) and improvement in the New York Heart Association (NYHA) class. Conclusions: KT significantly improves PH in ESKD patients on hemodialysis and can potentially normalize it. There is also improvement in overall cardiac functions, serum hemoglobin, and calcium levels. This translates to better physical endurance as evidenced by improvement in NYHA class post KT.